Do Temporary Business Tax Cuts Matter? : A General Equilibrium Analysis - Gbohoui, William (IMF Working Papers; Working Paper, 2019)
This paper develops a dynamic general equilibrium model to assess the effects of temporary business tax cuts. First, the analysis extends the Ricardian equivalence result to an environment with production and establishes that a temporary tax cut financed by a future tax-increase has no real effect if the tax is lump-sum and capital markets are perfect. Second, it shows that in the presence of financing frictions which raise the cost of investment, the policy temporarily relaxes the financing constraint thereby reducing the marginal cost of investment. This direct effect implies positive marginal propensities to invest out of tax cuts. Third, when the tax is distortionary, the expectation of high future tax rates reduces the expected marginal return on investment mitigating the direct stimulative effects.